2002
DOI: 10.1016/s0895-7061(02)03029-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age, risk factors, and cardiovascular and renal disease on arterial stiffness: clinical applications

Abstract: Age is the main clinical determinant of large artery stiffness. Central arteries stiffen progressively with age, whereas peripheral muscular arteries change little with age. A number of clinical studies have analyzed the effects of age on aortic stiffness. Increase of central artery stiffness with age is responsible for earlier wave reflections and changes in pressure wave contours. The stiffening of aorta and other central arteries is a potential risk factor for increased cardiovascular morbidity and mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
254
5
28

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(308 citation statements)
references
References 91 publications
(99 reference statements)
21
254
5
28
Order By: Relevance
“…The present results support previous clinical and epidemiological studies which prove that a sedentary life style, physical inactivity, smoking, dyslipidemia, and alcohol and sodium intake are also external factors influencing the development of hypertension (31)(32)(33).…”
Section: Discussionsupporting
confidence: 91%
“…The present results support previous clinical and epidemiological studies which prove that a sedentary life style, physical inactivity, smoking, dyslipidemia, and alcohol and sodium intake are also external factors influencing the development of hypertension (31)(32)(33).…”
Section: Discussionsupporting
confidence: 91%
“…16 Numerous cardiovascular risk factors, including diabetes, hypertension, hyperlipidemia, cigarette smoking and increasing adiposity, are also associated with increased arterial stiffness, often referred as 'premature arterial stiffening'. [20][21][22] The effect of adiposity on arterial stiffness may begin during childhood and affect the vascular system at a very early stage of vascular aging. 23 Several pre-existing risk factors, including diabetes, hypertension and dyslipidemia, may particularly increase the negative cardiovascular effects of elevated adiposity, causing greater CVD risk at an earlier age in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…12 These changes may be further exacerbated by hypertension. 16,17 Studies investigating flow-mediated vasodilation (FMD) have shown that moderate-intensity AE significantly increased FMD in hypertensive and normotensive subjects, likely mediated through augmented endothelial function. 18,19 There is also evidence that combined AE and RE training programs can improve endothelial function; 20 however, there is only one recent study that has shown an attenuated response to resistance forearm training in a cohort of hypertensive subjects, yet their results may have been confounded with the protocol acceptance of BP medications.…”
Section: Introductionmentioning
confidence: 99%